Analysis of Current Transport Mechanism in AP-MOVPE Grown GaAsN p-i-n Solar Cell - Wojciech Dawidowski; Beata Ściana; Katarzyna Bielak; Miroslav Mikolášek; Jakub Drobný; Jarosław Serafińczuk; Iván Lombardero; Damian Radziewicz; Wojciech Kijaszek; Arpád Kósa; Martin Florovič; Jaroslav Kováč; et al. (Energies, 2021)
Basic knowledge about the factors and mechanisms affecting the performance of solar cells and their identification is essential when thinking of future improvements to the device. Within this paper, we investigated the current transport mechanism in GaAsN p-i-n solar cells grown with atmospheric pressure metal organic vapour phase epitaxy (AP-MOVPE). We examined the electro-optical and structural properties of a GaAsN solar cell epitaxial structure and correlated the results with temperature-dependent current-voltage measurements and deep level transient spectroscopy findings. The analysis of J-V-T measurements carried out in a wide temperature range allows for the determination of the dominant current transport mechanism in a GaAsN-based solar cell device and assign it a nitrogen interstitial defect, the presence of which was confirmed by DLTFS investigation.